THE IMPACT OF VIRTUAL LABORATORIES ON DEVELOPING INTEGRATIVE CONCEPTS BETWEEN MATHEMATICS AND SCIENCE AMONG EIGHTH GRADE STUDENTS - Ibrahim, Azhar Ali Hussein; Ali, Zuher Ahmed (Guruku: Jurnal Pendidikan Profesi Guru, 2025)
This study aimed to investigate the impact of virtual laboratories on developing integrative concepts between mathematics and science among eighth-grade students. The research adopted an experimental design with three equivalent groups: the first experimental group studied mathematics using virtual laboratories, the second experimental group studied science using virtual laboratories, and the control group studied using the traditional method. The sample consisted of 83 eighth-grade students from basic education schools in Duhok Governorate for the academic year 2024-2025. The researchers prepared an integrative concepts test consisting of 18 items distributed equally across three concept elements (definition, discrimination, application). The results revealed statistically significant differences between the three groups in the post-test of integrative concepts in favor of both experimental groups, with no significant difference between the two experimental groups themselves. Additionally, both experimental groups showed significant improvement in their integrative concepts understanding from pre-test to post-test. The effect sizes were large, confirming the educational importance of these differences. Based on these findings, the researchers recommended providing the necessary infrastructure for implementing virtual laboratories in schools, training teachers to use them effectively, and developing curriculum materials that highlight the connections between mathematics and science concepts. The study suggested conducting further research on the impact of virtual laboratories on other educational aspects and in different educational stages.